Digital News Dynamics: Investigating the Impact on Public Opinion Formation in Pakistan (Journal of Asian Development Studies, 2023)
This study explores the complex relationship between digital news consumption and public opinion formation in Pakistan. Employing a quantitative approach, the research focused on adult digital news consumers across Pakistan, utilizing stratified sampling for a diverse demographic representation. The study formulated and tested several hypotheses related to the frequency of digital news consumption, source credibility, social media engagement, content diversity, and the mediating role of digital literacy. Findings from a structured questionnaire survey indicate that all these factors significantly influence the formation of public opinion. The study also highlights the pivotal role of digital literacy as a mediator in this process. These insights extend the application of theories such as agenda-setting and uses and gratifications in the context of digital media. The study contributes to the academic discourse on media influence in the digital era and offers practical implications for policymakers and media practitioners. It underscores the need for strategies promoting media literacy and responsible news consumption. The study acknowledges its limitations, including reliance on self-reported data and its focus on Pakistan, which may affect the generalizability of the findings. Future research avenues include comparative studies across countries and longitudinal analyses to understand evolving digital news consumption patterns.